Computational Modelling of Bifurcations and Instabilities in Fluid Dynamics - Gelfgat, Alexander (Computational Methods in Applied Sciences, 2019)
Instabilities of fluid flows and the associated transitions between different possible flow states provide a fascinating set of problems that have attracted researchers for over a hundred years. This book addresses state-of-the-art developments in numerical techniques for computational modelling of fluid instabilities and related bifurcation structures, as well as providing comprehensive reviews of recently solved challenging problems in the field. .